COVID-19-related impact on mental health and career uncertainty in student-athletes—Data from a cohort of 7,025 athletes in an elite sport high school system in Sweden - Håkansson, Anders; Moesch, Karin; Kenttä, Göran (Frontiers in Sports and Active Living, 2022)
Objectives: Mental health consequences and behavior change has been described in elite athletes following the vast impact of the COVID-19 pandemic on the world of sports. However, most study samples have been of limited size, and few studies have assessed student-athletes. This study aimed to analyze perceived mental health impact, measured as clinical degree of depression and anxiety, worry about one’s sport and about one’s career, and behavioral change with respect to video gaming behavior, in high-school athletes in Sweden. Methods: Data on anxiety and depression as well as on perceived behavioral changes during COVID-19 were collected from students at sports high schools in Sweden (N=7,025) in February 2021, during the ongoing COVID-19 pandemic. Results: Sixteen and 14 percent met criteria of moderate/severe depression and anxiety, respectively. Many respondents reported feeling mentally worse during the pandemic (66 percent), and were worried about the future of their sport (45 percent) or about their own future in sports (45 percent). Increased gaming behavior during COVID-19 was reported by 29 percent. All mental health variables were significantly more common in women, except increased gaming (more common in men). Being worried about one’s career was less common in winter sports, more common in team sports and more common in older student-athletes, and associated with both depression and anxiety in regression analyses. Discussion: Self-reported mental health impact of COVID-19 is substantial in student-athletes, and even more so in women and in team sports. The lower impact in winter athletes suggests a moderating effect of the seasons in which the COVID-19 outbreak occurred.